Identification and quantification of environmental radionuclides and the use of Monte Carlo codes for gamma-ray detector optimisation - Ajani, Mistura Bolaji (My University, 2021)
The study to determine the radioactivity levels and elemental concentrations of soil samples collected in Chad was undertaken. The objective was to ascertain pos sible contribution to the enhancement of naturally occurring and/or man-made radionuclides, including toxic heavy metals in the area. Moreover, the HPGe gamma-ray counting system was efficiency calibrated using standard sources and verified by Monte Carlo simulations to correct for the summing effect. A low back ground Hyper Pure Germanium detector was used to determine the radioactivity levels in 20 soil samples collected from Chad in Central Africa. The following radionuclides, 238U, 235U, 232Th, 137Cs and 40K were identified and their activity concentrations were determined. The results show that samples S1-S16 with an average activity concentration range of 2.4 to 35.3 Bq/kg is lower compared to sample S17-S20 with range of 130.9 to 239.3 Bq/kg for 235U. For 232Th and 40K, the observation was not similar to the trend as shown with 235U. The distribu tion of activity concentrations in the samples were found to be relatively lower in sample S1-S16 while sample S17-S20 were found to be relatively higher. Ad ditionally, the results obtained for 238U, 232Th and 40K were compared with the world average value 35, 30 and 400 Bq/kg, respectively, specified by UNSCEAR (2000). In order to evaluate the radiological hazard of the natural radionuclides, the radium equivalent activity, external and internal hazard indices, annual effec iii tive dose equivalent (AEDE) and excess lifetime cancer risk (ELCR) have been calculated with average of 111 (Bq/kg), 0.30 and 0.54, 0.41 (mSv/y) and 1.42 (×10−3 ) respectively. Correlation between 238U vs 232Th, 40K vs 238U, and 40K vs 232Th were investigated, the result showed good correlation for 238U vs 232Th and 40K vs 238U while 40K vs 232Th gives poor correlation. From the 20 samples collected in Chad, 10 samples were selected for further analysis using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). The uranium and potassium re sults were correlated with the data from gamma-spectroscopy and the uranium were found to have strong positive correlation while potassium have poor cor relation. ICP-MS analysis revealed the presence of various toxic elements, Cu (3-225 mg/kg), Mo (0.15-15.50 mg/kg), Co (1-35 mg/kg), Sn (0.29-8.89 mg/kg), Sb (BDL-1.01 mg/kg), Se (0.04-0.44 mg/kg), As (0.41-6.09 mg/kg); U (0.19-64.37 mg/kg); Pb (4-59 mg/kg); Cd (0.004-1.896 mg/kg) and Hg (0.07-5.57 mg/kg), re spectively. Some of the elemental concentrations for Cu, Mo and Hg were higher than the Maximum Allowable Limit (MAL) for some samples, while others were within the safe limit. The observed Hg with average of 2 mg/kg was found to be higher than the FAO/WHO recommended/safe limit of 0.93 mg/kg. To val idate the experimental results due to coincidence summing effect and efficiency calibration, GEANT4 and FLUKA Monte Carlo codes were utilised to test these parameters. For the full-energy peak efficiency, the following reference sources 40K, 22Na, 137Cs, 60Co and 152Eu were used, while both the 60Co and 22Na were further employed to validate coincidence summing corrections. This comparison shows how two different Monte Carlo codes agree with experimentally obtained efficiency of the detector and ultimately applied GEANT4 for coincidence sum ming corrections. Also, coincidence summing correction factor were calculated for iv both 238U and 232Th using EFFTRAN software and the correction factors show 65-100% confidence level.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Science, School of Physics, University of the Witwatersrand, Johannesburg, 2021